Integrasi Nilai Keislaman dalam Tata Kelola Kebijakan Sosial pada Masyarakat Multikultural: Perspektif Islam Lokal di Kota Padangsidimpuan - Riski Hastuti Ritonga; Nur Azizah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This article examines the integration of Islamic values into social policy governance within the multicultural society of Padangsidimpuan City. This research uses a qualitative approach with empirical methods through interviews, observations, and analysis of local policy documents. The results indicate that Islamic values such as justice, welfare, deliberation, and social solidarity have been internalized in the practice of local government social policies, although they have not been explicitly formalized in regulations. The integration of local Islamic values serves as a foundation for social ethics that strengthens policy legitimacy and maintains harmony within a multicultural society. This research confirms that local Islam has a strategic contribution to strengthening social policy at the local level.